Validation of two UHPLC-MS/MS methods for fast and reliable determination of quinolone residues in honey - KÖK YETİMOĞLU, ECE (TAYLOR & FRANCIS LTD, 2021)
Antibiotic usage for beekeeping, including quinolones, can lead to residues in honey and these residues usually result from the drugs used in the treatment of American or European foulbrood diseases. Residues in honey may cause allergic reactions as well as increased antibiotic resistance. Within this study, rapid and breakthrough analysis methods were developed using UHPLC-ESI-MS/MS and sample preparation processes were minimised. Practical, low cost, time-effective analysis was provided utilising 'dilute & shoot' methodology and a QuEChERS-based procedure has been developed alternatively for improved sensitivity. Recovery values were 85%-112% for the 'dilute & shoot' method, and 82%-117% for the modified QuEChERS method. For accuracy studies, RSD% values were between 0.7% and 13.4% for both methods in intra-day and inter-day precision studies. CC alpha (1.1 mu g/kg and 0.6 mu g/kg) and CC beta (1.2 mu g/kg and 0.6 mu g/kg) mean values were calculated for the 'dilute & shoot' and QuEChERS method, respectively. These novel methods achieved simultaneous quantification of 21 quinolones in 7 min with high specificity and were used to analyse 50 honey samples. Quinolone residues were found in samples, and enrofloxacin, danofloxacin, pipemidic acid, lomefloxacin, cinoxacin, and ciprofloxacin were quantified.
Keywords: Quinolones; UHPLC-ESI -MS; MS; honey; QuEChERS; dilute & shoot